Broadening the Conversation: Critical Questions Amidst Narrowing Views of Classroom Reading Instruction - Stouffer, Joe; Sutherland, Kathie; Matczuk, Allyson (Language and Literacy / Langue et littératie, 2026)
Framing the Manitoba Association of School Psychologists position statement as an illustrative case of recent debates on classroom literacy instruction, the authors respond to recent calls for universal structured literacy approaches heard from sponsors of the Science of Reading movement. In hope of eliciting critical and informed discourse among policy makers and instructional leadership across Canada, the authors weave their discussion drawing on recent research with expansive questions for leadership to pose with teachers and other stakeholders which interrogate: a) the debates between and invocations of “science” to endorse or discredit structured and balanced approaches to literacy instruction; b) calls to teach all students to read in a one-size-fits all manner using approaches derived from interventions designed for students experiencing reading difficulties; and c) reductive views of literacy teaching and learning. While acknowledging the foundational importance of code-focused instruction to reading development, the authors challenge the soundness of narrowed approaches to literacy instruction.